Globalization Impacts on Socio-Economic Change: A Social Science Education Perspective in Indonesia - Siti Noviyanti; Tria Putri Agustin (Yayasan Cerdas Pedia Indonesia, 2025)
This study examines how globalization-driven socio-economic shifts in 2024–2025 impact Social Science Education (IPS) in Indonesia. As the nation pursues